2011
DOI: 10.1103/physrevlett.107.245501
|View full text |Cite
|
Sign up to set email alerts
|

van der Waals Interactions in Ionic and Semiconductor Solids

Abstract: van der Waals (vdW) energy corrected density-functional theory [Phys. Rev. Lett. 102, 073005 (2009)] is applied to study the cohesive properties of ionic and semiconductor solids (C, Si, Ge, GaAs, NaCl, and MgO). The required polarizability and dispersion coefficients are calculated using the dielectric function obtained from time-dependent density-functional theory. Coefficients for "atoms in the solid" are then calculated from the Hirshfeld partitioning of the electron density. It is shown that the Clausius-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
180
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 167 publications
(198 citation statements)
references
References 32 publications
16
180
0
2
Order By: Relevance
“…For instance, Zhang et al demonstrated a substantial linear dependence of α Si and C 6 Si−Si in zinc blende silicon on the lattice constant using TD-DFT calculations. 80 This behavior cannot be explained by the coordination of the silicon, because this is unchanged throughout the lattice contraction, but rather can be related to the change in the electronic band gap. Nonlinear dependence of vdW parameters on the lattice constant can be observed in semiconductors, such as Ge, where the small band gap becomes zero upon the metallic phase transition induced by the lattice contraction.…”
Section: Conceptual Understanding Of Vdw Interactions In Molecules Anmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, Zhang et al demonstrated a substantial linear dependence of α Si and C 6 Si−Si in zinc blende silicon on the lattice constant using TD-DFT calculations. 80 This behavior cannot be explained by the coordination of the silicon, because this is unchanged throughout the lattice contraction, but rather can be related to the change in the electronic band gap. Nonlinear dependence of vdW parameters on the lattice constant can be observed in semiconductors, such as Ge, where the small band gap becomes zero upon the metallic phase transition induced by the lattice contraction.…”
Section: Conceptual Understanding Of Vdw Interactions In Molecules Anmentioning
confidence: 99%
“…The other limit assumes Na + and Cl − ions, yielding a significantly reduced polarizability of 21.6. 80 The large difference between these two limits is caused by the change in the polarizability from 167.7 for neutral Na atom to 0.9 for Na + . Measurements of dielectric properties 81 and high-level calculations 82 demonstrate that the polarizability of NaCl solid is in fact closer to the sum of Na + and Cl − ions.…”
Section: Conceptual Understanding Of Vdw Interactions In Molecules Anmentioning
confidence: 99%
See 2 more Smart Citations
“…[56,57] For an accurate description of all of the non-covalent interactions, a method must therefore be able to address the whole range of interactions. Accordingly, the vdW correction methods are tested for ionic crystals of LiH, LiF, LiCl, NaF, NaCl, NaI, KCl, KI, and MgO.…”
Section: Ionic Crystalsmentioning
confidence: 99%